Distal Radius Fracture Subsidence after Nonoperative Treatment - Alzouhayli, Kenan; Samade, Richard; Sitton, Beau; Bates, Nathaniel; Goyal, Kanu S. (Journal of Wrist Surgery, 2024)
Background Our primary aim was to identify risk factors for subsidence development in nonoperatively treated distal radius fractures (DRFs). Secondary aims of the study included comparisons of subsidence progression over time with respect to DRF radiographic parameters.Materials and Methods A retrospective cohort study of 70 patients with DRFs treated nonoperatively and followed for a minimum of 12 weeks was performed. Of the 70 patients, 29 had subsidence and 41 did not have subsidence. Radiographic measurements assessed the radial height (RH), ulnar variance (UV), volar tilt (VT), and radial inclination (RI). Outcome measures included demographics, injury characteristics, closed reduction, and radiographic measurements.Results Nearly 95% of DRF subsidence occurred within the first 6 weeks after nonoperative treatment. The mean age of the 41 patients without DRF subsidence was 57.6 ± 16.8 years, and 31/41 (76%) patients were females. Conversely, the mean of the 29 patients with DRF subsidence was 63.8 ± 17.5 years, and 22/29 (76%) patients were females. Fractures requiring closed reduction were associated with more overall subsidence (p = 0.0009) and subsidence within the first 2 weeks posttreatment. Type C and comminuted fractures were associated with DRF subsidence (p = 0.02 and 0.01, respectively). The initial radiographic parameters and step-off measures were not associated with a higher risk of subsidence (p ≥ 0.05). Significant differences between subsidence progressions with respect to RH, UV, VT, and RI were observed.Conclusion Most DRF subsidence occurs within the first 6 weeks of nonoperative treatment. Closed reduction, comminution, and AO fracture type are predictors of subsidence development. Moreover, DRF subsidence progresses at different rates depending on the radiographic parameter assessed.
Keywords: displacement; distal radius fracture; nonoperative; radial height; subsidence; volar tilt; Level of Evidence: IV, therapeutic